Semi-Immersive Virtual Reality (VR) as Media in Teaching English at an Indonesian Private University - Nasrullah Abdullah; Patahuddin Hakim; Muhaimin Abdullah (Eduvelop: Journal of English Education and Development, 2026)
This study examines the efficacy of semi-immersive virtual reality (VR) in enhancing English language learning to address the challenges learners face in traditional educational settings. By employing 360-degree web-based imagery, we sought to create a more captivating and engaging educational experience. The research involved 20 students from the English Education Study Program, who participated in a series of immersive learning activities designed to augment their linguistic skills. Data collected through comprehensive surveys revealed a significant preference for the semi-immersive VR approach among participants. They expressed enthusiasm not only for the material's visual appeal but also for the comfort and flexibility the VR environment provided during the learning process. These insights suggest that integrating visual and interactive elements into language education can foster a deeper connection to the material, thus enhancing motivation and retention. The results show that learners found the semi-immersive VR technique helpful in enhancing literacy-related learning experiences, particularly by raising awareness of digital literacy, engagement, and comprehension. Although these results demonstrate the educational potential of VR, more studies using objective literacy tests are required to confirm its effect on real skill development. Moreover, this study underscores the transformative potential of semi-immersive VR in language education, highlighting its capacity to enhance engagement and effectiveness in the learning environment. In conclusion, our results advocate for the strategic integration of advanced technological resources into English language curricula, which could lead to improved student outcomes and a more enriched educational experience. Such advancements are crucial for preparing students to meet the demands of an increasingly digital world.